2021
DOI: 10.7717/peerj.12411
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas hydrophila infection induces Toll-like receptor 2 (tlr2) and associated downstream signaling in Indian catfish, Clarias magur (Hamilton, 1822)

Abstract: Motile Aeromonas septicaemia (MAS), caused by Aeromonas hydrophila, is one of the most significant bacterial disease responsible for mortality in Indian catfish, Clarias magur, a potential aquaculture species in the Indian subcontinent. In fish, innate immunity elicited by pathogen recognition receptors (PRRs) plays an important role in providing protection against bacterial infection. Information on PRRs including Toll-like receptors (tlrs) and their response to bacterial pathogens remains unexplored in magur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The genes TNF , TLR2 , IL8 and MHCII in these pathways were also downregulated. They are associated with the body function of the natural cell-killing ability and T-cell immunity, and their downregulation demonstrated that poly (I:C) would regulate these genes, and then enhance the natural cell-killing ability, affect the T-cell immunity and decrease apoptosis induced by endogenesis [ 1 , 45 , 46 , 47 ]. At 48 h, poly (I:C) injection might, on the one hand, enhance the spleen energy metabolism, while, on the other hand, induce some injury, such as virus infection, which is a finding that could be supported by the results that found that the disease-related pathways were significantly enriched, the damaged presentation gene TXNRD was upregulated [ 36 ] and HBA was downregulated [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genes TNF , TLR2 , IL8 and MHCII in these pathways were also downregulated. They are associated with the body function of the natural cell-killing ability and T-cell immunity, and their downregulation demonstrated that poly (I:C) would regulate these genes, and then enhance the natural cell-killing ability, affect the T-cell immunity and decrease apoptosis induced by endogenesis [ 1 , 45 , 46 , 47 ]. At 48 h, poly (I:C) injection might, on the one hand, enhance the spleen energy metabolism, while, on the other hand, induce some injury, such as virus infection, which is a finding that could be supported by the results that found that the disease-related pathways were significantly enriched, the damaged presentation gene TXNRD was upregulated [ 36 ] and HBA was downregulated [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…EF‐1α was found to be the best candidate gene for analysis of Toll‐like receptor 3 and melanoma differentiation associated gene in CIK ( Ctenopharyngodon idella kidney) cell culture post Grass carp reovirus infection (Su et al, 2011). EF‐1α was used as RG for relative expression quantification of TLR2 and its downstream signalling molecule (Muduli, Paria, et al, 2021; Muduli, Rathore, et al, 2021). Paria et al (2016) also suggested EF‐1α and 18S to be the best RG in Asian seabass following V. alginolyticus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Each sub‐group was maintained in three experimental tanks containing 10 fish each. Our previously isolated and characterized A. hydrophila strain 9C (Muduli et al, 2020, 2021b; Muduli, Rathore, et al, 2021) was used in this study. In A. hydrophila injected sub‐group, fish were injected with A. hydrophila at a concentration of 1 × 105 cfu/ fish in 100 µl PBS by intra‐peritoneal route.…”
Section: Methodsmentioning
confidence: 99%
“…TLR13, TLR22, TLR25, and TLR26 in Walking catfish ( Clarias batrachus ) ( Priyam et al, 2020 ). Furthermore, researchers have also examined what occurs when a pathogenic bacterium, virus, or ligand is used as a stimulator, with regard to expression profiles and signalling cascade genes ( Jiang et al, 2020 ; Muduli et al, 2021 ; Wang et al, 2021 ). TLR ligands remain substantially unknown, especially in cartilaginous fish and lobe-finned fish ( Nie et al, 2018 ; Smith, Rise & Christian, 2019 ).…”
Section: Survey Methodologymentioning
confidence: 99%